2022
DOI: 10.3389/fonc.2022.999606
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent clinical outcomes following afatinib treatment in NSCLC patients harboring uncommon epidermal growth factor receptor mutation

Abstract: BackgroundUncommon epidermal growth factor receptor (EGFR) mutations consist of a heterogeneous population of molecular alterations, and the available clinical data on the outcomes of patients with non-small-cell lung cancer (NSCLC) harboring uncommon EGFR mutations following afatinib treatment are limited. The purpose of this pooled analysis was to investigate the clinicopathological features of patients with uncommon EGFR mutations (um-EGFRms) along with their treatment response and survival outcomes followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…S768I is an uncommon mutation and accounts for 1.5 %–3 % of untreated EGFR-mutated tumours [ 24 , 25 ]. Patients harbouring S768I exhibit good TKI treatment responses and prognosis [ 26 ]. Multiple studies have shown that afatinib is effective for NSCLC patients with the S768I mutation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…S768I is an uncommon mutation and accounts for 1.5 %–3 % of untreated EGFR-mutated tumours [ 24 , 25 ]. Patients harbouring S768I exhibit good TKI treatment responses and prognosis [ 26 ]. Multiple studies have shown that afatinib is effective for NSCLC patients with the S768I mutation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%